Clinical utility of oximetric parameters to identify a high‐risk phenotype of moderate‐severe Obstructive Sleep Apnea (OSA). (3rd September 2020) - Labarca, Gonzalo; Dreyse, Jorge; Salas, Constanza; Letelier, Francisca; Schmidt, Alexia; Rivera, Francisca; Jorquera, Jorge
Abstract: It is unclear if oximetric parameters, such as total time of SpO2 < 90%, (T90), oxygen desaturation index‐3% (ODI), minimum SpO2, are able to describe a high‐risk subtype of cardiovascular (CV) comorbidities in patients with Obstructive sleep apnea (OSA) beyond the apnea‐hypopnea index. Objective: To analyzed oximetric variables in patients with moderate‐severe OSA to assess their predictive value regarding as hypertension, type 2 diabetes mellitus (T2DM), coronary heart disease (CHD) and CV mortality. Methods: Using data from SantOSA cohort, we develop receiver operating characteristic curve and area under the curve (AUC) for each parameter, defining the proposed cutoff point in a training set. Then, in a validation set with a 5 years follow‐up, we evaluate the clinical differences between groups using the proposed cutoff. We also calculated adjusted Hazard Ratios (HR) of mortality using a Cox regression model. Results: About 965 patients with moderate‐severe OSA (525 in training and 440 in validation group) were included. The best AUC was achieved with T90 (AUC = 0.66) and ODI (AUC = 0.61). Proposed cutoffs of T90 were hypertension: 10%, T2DM: 20%, CHD: 15%, meanwhile, proposed cutoff of ODI was ≥ 30 ev for hypertension and T2DM. Regarding CV mortality, T90 ≥ 20% was independently associated with an adjusted HR 2.44 (CI, 1.21‐4.94), P ‐value = 0.01, meanwhile, ODI ≥ 30 ev. reported and adjusted HR 1.59 (CI, 0.75‐3.39), P ‐value = 0.22. Conclusion: In patients with moderate‐severe OSA, oximetric parameters, especially T90 ≥ 20% remained a predictor of mortality after adjusting for a range of demographic and disease predictors.